Noble Metal Nanoparticle‐Based Aptasensors: A Powerful Tool for Exosomal Detection - Jingyu Sun; Wei Hu; Nuo Xu; Jonathan Makris; Felicia Spadavecchia; Hongjun Wang (Advanced Sensor Research)
Abstract Exosomes, secreted by various types of cells, play a crucial role in cell‐to‐cell communication by transporting essential molecular cargos that largely mirror the pathophysiological attributes of their parent cells. Increasing evidence has shown that exosomes emerge as the reliable early biomarkers for different diseases. Clearly, exosomal detection with a high sensitivity and specificity becomes highly essential to advance the understanding of disease progression and to develop early diagnostic modalities. Among different types of biosensors, aptasensors have received significant attention as the diagnostic tools considering their programmability and targeting ability. Noble metal nanomaterials possess distinctive physicochemical properties, allowing for ready functionalization with aptamers via both physical adsorption and chemical immobilization. By utilizing the aptamers as the recognition elements, noble metal nanoparticle‐based aptasensors offer a promising platform for rapid, cost‐effective, and sensitive in situ detection of exosomes. In this review, the progress will summarized in exosomes as a biomarker for diseases and the recent advances in the use of noble metal nanoparticle/aptamer‐based sensors for analysis of exosomes and other extracellular vesicles.